2023
DOI: 10.1088/1674-1056/aca202
|View full text |Cite
|
Sign up to set email alerts
|

Different roles of surfaces’ interaction on lattice mismatched/matched surfaces in facilitating ice nucleation

Abstract: The freezing of water is one of the most common processes in nature and affects many aspects of human activity. Ice nucleation is a crucial part of the freezing process and usually occurs on material surfaces. There is still a lack of clear physical pictures about the central question how various features of material surfaces affect their capability in facilitating ice nucleation. Via molecular dynamics simulations, here we show that the detailed features of surfaces, such as atomic arrangements, lattice param… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…However, some studies found that several materials with the same lattice as ice crystals, such as barium fluoride and cuprous bromide, are not effective heterogeneous ice nucleating materials [12,13]. Therefore, the lattice matching mechanism is insufficient to explain the ice nucleation on the substrate [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies found that several materials with the same lattice as ice crystals, such as barium fluoride and cuprous bromide, are not effective heterogeneous ice nucleating materials [12,13]. Therefore, the lattice matching mechanism is insufficient to explain the ice nucleation on the substrate [14].…”
Section: Introductionmentioning
confidence: 99%